Character Improvement of Red Rice (Oryza Sativa L.) Cv. Barak Cenana by Mutagenesis using Gamma Irradiation - Aloysia Sri Pujiyanti; Bintang Kerta Wijaya; Ida Bagus Made Artadana; Popy Hartatie Hardjo; Maria Goretti Marianti Purwanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Red rice cv. Barak Cenana is a local Indonesian rice which is widely planted in Tabanan Regency, Bali. Barak Cenana red rice has potential as a functional food because it contains a lot of nutrients. However, this rice has an unfavorable character, such as long harvest time so that it can only be harvested once a year, and tall stature that causes plants to lodge easily, reducing its productivity. This study aims to determine the effect of gamma rays on growth and development as well as changes in character to obtain mutants plants that have better character. In this research, Barak Cenana seeds were irradiated using gamma rays with irradiation doses of 100 gy, 200 gy, 400 gy, and 800 gy. Furthermore, radiated seeds were planted in the greenhouse and characterized during the vegetative and generative phases including shoot length, harvest time, chlorophyll content, the number of productive tillers, the number of grain contents, the weight of 1,000 seeds, and the polymorphism profile using Random Amplified Polymorphic DNA Analysis (RAPD). The results of this study indicate that all radiation doses produce plants with random characters. Mutations using gamma rays at doses of 100 gy and 400 gy produced plants with better phenotypic characters than wild-type that is shorter plants, shorter harvest times, and more grain content. In addition, the results of the RAPD analysis confirm that there are genetic changes in irradiated rice. This mutants has the potential to reproduce germplasm and to obtain the next generation of mutants that have higher productivity and shorter plant heights.